"Sea Peoples" up-to-date : new research on transformations in the Eastern Mediterranean in the 13th-11th centuries BCE : proceedings of the ESF-Workshop held at the Austrian Academy of Sciences, Vienna, 3-4 November 2014 - Fischer, Peter M.; Bürge, Teresa, 1986- (Denkschriften der Gesamtakademie ;, 2017)
This volume presents the outcomes of the European Science Foundation workshop "Sea Peoples" Up-to-Date. New Research on Transformations in the Eastern Mediterranean in the 13th-11th Centuries BCE", which took place in November 2014 at the Austrian Academy of Sciences in Vienna. It offers up-to-date research on the Sea Peoples phenomenon during the so called "crisis years" at the end of the Bronze Age. This period encompasses dramatic changes in the political and cultural landscape of mainly the Eastern Mediterranean around 1200 BCE and most of the 12th century BCE. In geographical terms, these changes are noticeable in a vast area stretching from the Italian peninsula over the Balkans, the Aegean, Anatolia and Cyprus, to the Levant and Egypt. The term "Sea Peoples phenomenon" should be considered as an encompassing term, which- in addition to the written records on hostile activities of various ethnic groups in the Eastern Mediterranean- is synonymous with the effect of this turbulent period as reflected in the material remains. As a consequence, these events ended the Late Bronze Age, the first period of "internationalism" in human history.